PENINGKATAN HASIL BELAJAR TEMATIK MENGGUNAKAN METODE KERJA KELOMPOK KELAS III SDN 13 TELIDIK BENGKAYANG - Sepion, Zakeus; Sugiyono, Sugiyono; Tampubolon, Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to describe the improvement of student learning outcomes in Thematic learning by using group work method in class III State Elementary School 13 Telidik, Bengkayang Regency. The research method used is descriptive, research form of classroom action research, nature of collaborative research. Subjects in this study were teachers as researchers and students class IIII which amounted to 15 people. Data collection techniques used are direct observation and document observation .. The data collection tool used is the observation sheet and student evaluation sheet. , The data of the teacher's score score in planning and executing the learning is analyzed using the average formula. This study was conducted two cycles, the results obtained are the ability of teachers in planning the learning cycle I is 3.53 and cycle II 3.85. The ability of teachers in implementing learning in the first cycle that is 3.48, increased to 3.87 cycle II. An increase in learning outcomes in the first cycle average of 85.60 to 91.13 in the second cycle. The conclusion in this research is there is improvement of thematic learning result by applying group work method in class III elementary school 13 Telidik, Bengkayang. Keywords: Group Work, Learning Outcomes, Thematic Learning.